Family Support in Victims of Children of Sexual Violence in Indonesia - Februanti, Sofia; Kartilah, Tetet (International Journal of Innovative Research in Medical Science, 2019)
Every child has the right to survival, to grow and develop and has the right to protection from violence and discrimination. However, there are still many problems faced today, especially in Indonesia.This study aims to determine family support for girls who are victims of sexual violence. This study uses qualitative research methods with an in-depth interview approach with audio recordings, field notes, documentation. Participants in this study were families who had family members/girls victims of sexual violence. Sampling using purposive sampling technique that fits the inclusion criteria. The interview was recorded and made the word for word transcription. Transcripts of interviews were analyzed by Colaizzi's steps. The results of the study showed that there were four themes namely family informational support, family assessment support, family instrumental support, family emotional support. Family support is needed by girls who are victims of sexual violence to help their future survival.